2022
DOI: 10.1111/bjd.20979
|View full text |Cite
|
Sign up to set email alerts
|

Children with atopic dermatitis show increased activity of β‐glucocerebrosidase and stratum corneum levels of glucosylcholesterol that are strongly related to the local cytokine milieu

Abstract: Summary Background Atopic dermatitis (AD) is characterized by immune dysregulations and an impaired skin barrier, including abnormalities in lipid organization. In the stratum corneum (SC), β‐glucocerebrosidase (GBA) mediates transformation of glucosylceramide (GlcCER) into ceramide (CER) and cholesterol into glucosylcholesterol (GlcChol). Alteration in GBA activity might contribute to skin barrier defects in AD. Objectives To investigate GBA activity in the SC of children with AD before and after topical cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
(96 reference statements)
1
12
0
Order By: Relevance
“…This is not unexpected, considering that AD is characterized by a compromised skin barrier and dry skin, both of which are influenced by the composition and organization of intercellular lipid matrix as well as the presence on hygroscopic NMF in the SC. [1][2][3] A broad range of lipid biomarkers, such as the (relative) composition of sphingoid bases (SB's), 7 specific lipid classes or their relative composition 8,11,71 and enzymes involved in lipid biosynthesis [18][19][20] showed a strong correlation with the skin barrier function. The application of comprehensive lipidomic analysis has enabled progress in lipid research, revealing that not only lipid (sub)classes but also the carbon chain length in FFA and CER may influence skin barrier function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not unexpected, considering that AD is characterized by a compromised skin barrier and dry skin, both of which are influenced by the composition and organization of intercellular lipid matrix as well as the presence on hygroscopic NMF in the SC. [1][2][3] A broad range of lipid biomarkers, such as the (relative) composition of sphingoid bases (SB's), 7 specific lipid classes or their relative composition 8,11,71 and enzymes involved in lipid biosynthesis [18][19][20] showed a strong correlation with the skin barrier function. The application of comprehensive lipidomic analysis has enabled progress in lipid research, revealing that not only lipid (sub)classes but also the carbon chain length in FFA and CER may influence skin barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…18 Kezic et al found increased activity of β-glucocerebrosidase (GBA) and elevated levels of its enzymatic product glucosylcholesterol (GlcChol) in the scTS of patients with AD. 19 Both GBA activity and GlcChol levels were correlated with TEWL and the levels of proinflammatory IL-1 cytokines. Importantly, GBA activity and GlcChol levels normalized following corticosteroid therapy, suggesting their potential as biomarkers for monitoring therapeutic responses in AD.…”
Section: Lipids and Lipid Enzymesmentioning
confidence: 93%
See 1 more Smart Citation
“…Free SBs and their CERs were determined in a 2‐step procedure which is described in detail elsewhere 21 . Briefly, free SBs were separated from CERs by extraction with methanol:chloroform:ammonium formate buffer, yielding CERs in the lower phase and free SBs in the upper phase 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Free SBs and their CERs were determined in a 2-step procedure which is described in detail elsewhere. 21 Briefly, free SBs were separated from CERs by extraction with methanol:chloroform:ammonium formate buffer, yielding CERs in the lower phase and free SBs in the upper phase. 22 The CERs in the lower phase were subsequently deacylated to corresponding SBs by use of microwave-assisted hydrolysis in methanolic NaOH.…”
Section: Methods For Ceramide and Sphingoid Base Measurementsmentioning
confidence: 99%